Left ventricular longitudinal systolic dysfunction is associated with right atrial dyssynchrony in heart failure with preserved ejection fraction - Ibadete Bytyçi (Revista Portuguesa de Cardiologia, 2016)
Objective: We aimed in this study to assess the role of longitudinal left ventricular (LV) systolic function in heart failure with preserved ejection fraction (HFpEF) in delayed intra- and interatrial conduction time. Methods: In 85 consecutive patients with HFpEF (age 60±11 years, ejection fraction [EF] ≥45%), a complete M-mode echocardiographic and tissue Doppler imaging (TDI) study was performed. The times from the onset of the P wave on the ECG to the beginning of the A′ wave (PA) from the lateral and septal mitral and tricuspid annuli on TDI were recorded. The difference between these intervals gave the intra- and interatrial dyssynchrony. Based on mitral annular plane systolic excursion (MAPSE), patients were classified as having HFpEF with impaired (MAPSE ≤1.2 cm) or normal (MAPSE >1.2 cm) longitudinal systolic function. Results: Patients with impaired MAPSE were older (p<0.001), had higher LV mass index (p<0.001), greater left atrial (LA) minimum volume (p=0.007), reduced left atrial EF (p<0.001), higher E/e′ ratio (p=0.002), reduced lateral and septal e′ wave (p=0.005 and p=0.006, respectively), prolonged tricuspid PA′ (p=0.03) and significantly increased right atrial (RA) dyssynchrony (p=0.001) compared with normal MAPSE. MAPSE correlated with RA dyssynchrony (r=−0.40, p<0.001) but not with interatrial and LA dyssynchrony. Conclusion: In patients with HFpEF and impaired MAPSE, RA dyssynchrony is increased, compared to those with normal MAPSE. As patients with RA dyssynchrony are at higher risk for arrhythmia, assessment of this dyssynchrony may help to improve treatment, as well as to predict outcome in these patients. Resumo: Objetivos: Com este estudo pretendemos avaliar o papel da função sistólica longitudinal ventricular esquerda (VE) na insuficiência cardíaca com fração de ejeção preservada (ICFEp) no atraso da condução intra e interauricular. Métodos: Em 85 doentes consecutivos com ICFEp (60 ± 11 anos, FE ≥ 45%) foi realizado estudo ecocardiográfico completo modo-M e Doppler tecidular. O intervalo desde o início da onda P no ECG, até ao início da onda A no anel mitral lateral e septal e no anel tricúspide direito (em Doppler tissular) foi registado. A diferença entre estes intervalos forneceu a dessincronia intra e interauricular. Baseado na excursão sistólica de pico do anel mitral (ESPAM), os doentes foram divididos em ICFEp com disfunção (ESPAM ≤ 1,2 cm) e função sistólica normal longitudinal (ESPAM > 1,2 cm). Resultados: Os doentes com ESPAM baixa eram mais velhos (p < 0,001), tinham índice de massa VE mais elevado (p < 0,001), volume auricular esquerdo (VAE) superior (p = 0,007), FE auricular esquerda (AE) mais baixa (p < 0,001), rácio E/e’ mais elevado (p = 0,002), onda e’ lateral e septal reduzidas (p = 0,005 e p = 0,006), onda tricúspide PA prolongada (p = 0,03) e aumento significativo da dessincronia da aurícula direita (AD) (p = 0,001), quando comparados com doentes com ESPAM normal. A ESPAM estava correlacionada com a dessincronia AD (r = -0,40, p < 0,001), mas não com a dessincronia interauricular e da AE. Conclusão: Nos doentes com ICFEp e ESPAM baixa, existe dessincronia AD, quando comparada com os doentes com ESPAM normal. Como os doentes com dessincronia AD têm risco mais elevado de arritmia, a avaliação desta dessincronia pode ajudar a melhorar o tratamento, bem como a auxiliar na previsão prognóstica destes doentes. Keywords: Heart failure, Right atrial dyssynchrony, Systolic longitudinal function, Palavras-chave: Insuficiência cardíaca, Dessincronia auricular direita, Função sistólica longitudinal